Special base material for ultra-pure 409 series non-coping casting powder

By using the special base material of the super -pure 409 series of non -grinding and protective residue during the steelmaking process, the problem of stainless steel surface defects was solved, the non -grinding effect was achieved, and the quality of the cast blank was improved.

CN119346819AInactive Publication Date: 2025-01-24LUO YANG SHI KE FENG YE JIN XIN CAI LIAO YOU XIAN GONG SI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411921393.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of casting powder preparation, in particular to a special base material for ultra-pure 409 series non-coping casting powder. Comprising the following components in parts by weight: 11-15 parts of synergistic lime, 23-29 parts of calcium oxide, 25-32 parts of aluminum oxide, 12-16 parts of silicon dioxide, 9-13 parts of calcium fluoride, 6-8 parts of magnesium oxide, 0.8-1.2 parts of manganese carbonate, 2-5 parts of a zirconium oxide anti-erosion agent and 1-3 parts of a diboron trioxide viscosity modifier. 0.2 to 0.6 part by weight of a carbon powder reducing agent and 0.3 to 0.5 part by weight of a lithium oxide fluxing agent; wherein the synergistic lime is obtained by compounding active lime and praseodymium oxide according to the mass ratio of 10: (0.3-0.7) and then bonding with triethanolamine phosphate, the synergistic lime is adopted, the reaction rate of the active lime is controlled by compounding the reaction activity of the active lime higher than that of calcium oxide and praseodymium oxide, and the triethanolamine phosphate provides a protective layer and improves the surface quality of a casting blank; and the non-grinding effect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of protective slag preparation, in particular to a special base material for ultra-pure 409 series non-grinding protective slag. Background Art

[0002] 409 ultra-pure stainless steel, as a special alloy material, has shown excellent application value in multiple industrial fields with its unique combination of properties. It belongs to the ferritic stainless steel series, but compared with traditional ferritic stainless steel, 409 ultra-pure stainless steel has been finely regulated in chemical composition, removing more harmful impurity elements, thereby achieving a higher purity standard. This high purity not only improves the corrosion resistance of the material, but also enhances its mechanical strength and processing performance. In terms of corrosion resistance, 409 ultra-pure stainless steel shows good resistance to a variety of corrosive media, including stability in weak acids, weak alkalis and various salt solutions. In addition, 409 ultra-pure stainless steel also has good formability and weldability, making 409 ultra-pure stainless steel an ideal choice for many high-end application fields.

[0003] However, non-metallic inclusions are prone to appear in the steelmaking process. For example, if deoxidation is insufficient, the residual oxygen in the steel will combine with elements such as iron and chromium to form oxides. These oxides are pressed into the matrix during the rolling process to form surface defects, which in turn affect the quality of the ingot. In view of this, a special base material for ultra-pure 409 series non-grinding protective slag is provided. Summary of the invention

[0004] The object of the present invention is to provide a special base material of ultra-pure 409 series non-grinding protection slag to solve the problem of stainless steel surface defects mentioned in the above background technology.

[0005] To achieve the above object, the present invention provides a special base material for ultrapure 409 series non-grinding protective slag, comprising the following components in parts by weight: 11-15 parts by weight of synergistic lime, 23-29 parts by weight of calcium oxide, 25-32 parts by weight of aluminum oxide, 12-16 parts by weight of silicon dioxide, 9-13 parts by weight of calcium fluoride, 6-8 parts by weight of magnesium oxide, 0.8-1.2 parts by weight of manganese carbonate, 2-5 parts by weight of zirconium oxide anti-corrosion agent, 1-3 parts by weight of boron trioxide viscosity regulator, 0.2-0.6 parts by weight of carbon powder reducing agent and 0.3-0.5 parts by weight of lithium oxide flux; Among them, the enhanced lime is obtained by compounding active lime and praseodymium oxide in a mass ratio of 10:0.3-0.7 and bonding with triethanolamine phosphate.

[0006] As a further improvement of the technical solution, the specific preparation method of the enhanced lime is as follows: Praseodymium oxide and active lime powder are mixed in proportion, stirred continuously at 300-500 rpm / min with a stirrer to make them fully mixed, and then placed in a muffle furnace for calcination. After calcination, the mixture is crushed into powder with a particle size of less than 0.5 mm, and then added to a tetrahydrofuran solution containing triethanolamine phosphate, and stirred for 20-30 minutes. Dry at 100-120°C to constant weight. After drying, the mixture is ground and sieved to obtain enhanced lime.

[0007] Active lime is a specially treated lime. Compared with ordinary calcium oxide, it has higher reactivity, high porosity and large specific surface area. It can react quickly with non-metallic inclusions to form products that are easy to float, thereby effectively removing inclusions and greatly improving the purity of molten steel. Praseodymium oxide is a rare earth element oxide that can improve the fluidity of slag, help adsorb inclusions in molten metal, refine grains and improve the mechanical properties of metal.

[0008] Since active lime has a very high reactivity, when added to molten steel it will cause an overly violent reaction that is difficult to control, causing splashing or other safety hazards. Therefore, it is combined with rare earth element oxides to form a composite material that can effectively improve the reaction controllability of active lime and regulate its reaction rate. When praseodymium ions enter the crystal lattice of active lime, lattice defects are formed. These defects can serve as new active sites to inhibit the reaction of the active lime, thereby controlling its reaction rate.

[0009] In addition, active lime is extremely hygroscopic and prone to agglomeration, which will affect its activity and effect in the protective slag. Therefore, a layer of triethanolamine phosphate is bonded to the surface of the active lime to form a hydrophobic film on the surface of the active lime to reduce moisture absorption or reaction with moisture and carbon dioxide in the air. This is used to protect the active lime. Since triethanolamine phosphate contains multiple hydroxyl and phosphate groups, its hydroxyl groups will form hydrogen bonds with oxygen atoms on the surface of the active lime to form an adsorption layer, and the phosphate groups will form coordination bonds with calcium ions on the surface of the active lime, thereby forming a stable complex on the surface of the active lime, thereby improving the stability of the active lime.

[0010] In addition, since rare earth elements usually have high chemical reactivity, they can react with phosphorus-containing compounds at high temperatures to generate a phosphorus-containing compound. This phosphorus-containing compound can effectively adsorb non-metallic inclusions in the molten metal, such as oxides and sulfides, and gather them in the protective slag, thereby improving the purity of the metal and the quality of the casting. It can also adjust the viscosity of the slag to ensure that it forms a uniform, moderately fluid protective layer on the surface of the molten metal to prevent the entry of oxygen and moisture in the air, reduce the oxidation of the molten metal, and protect the stability of the composition of the molten metal.

[0011] As a further improvement of the technical solution, the calcination temperature of the muffle furnace is 400-600° C., and the calcination time is 2-4 hours.

[0012] As a further improvement of the technical solution, the mass fraction of the tetrahydrofuran solution containing triethanolamine phosphate is 4-6%.

[0013] As a further improvement of the technical solution, the mass ratio of the active lime to triethanolamine phosphate is 1:0.01-0.05.

[0014] As a further improvement of the technical solution, the specific preparation method of the special base material for protective slag is as follows: Add synergistic lime, calcium oxide, aluminum oxide, silicon dioxide, calcium fluoride, magnesium oxide, manganese carbonate, zirconium oxide anti-corrosion agent, boron trioxide viscosity regulator, carbon powder reducing agent and lithium oxide flux into the mixer, mix all the raw materials thoroughly, put the mixed raw materials into a high-temperature furnace, set the temperature curve for heating, keep the heat for 1-3 hours after the raw materials are completely melted, use the rapid cooling method to quickly solidify them, then use a crusher to break them into small pieces, and sieve the broken small pieces through sieves of different apertures to obtain the special base material of ultra-pure 409 series non-grinding protective slag.

[0015] As a further improvement of the technical solution, the filling amount of the mixer is 45-55% of the total capacity, the mixing speed is 30-50 rpm / min, and the mixing time is 20-30 min.

[0016] As a further improvement of the technical solution, the temperature curve includes three stages: the preheating stage is gradually heated from room temperature to 200-300°C, with a heating rate of 5-10°C / min; the heating stage is heated from 300°C to 800-1000°C, with a heating rate of 10-15°C / min; the melting stage is heated from 1000°C to the final melting temperature of 1400-1500°C, with a heating rate of 1-5°C / min.

[0017] As a further improvement of the technical solution, the crushing speed of the crusher is 500-1000rpm / min, and the crushing time is 5-10min.

[0018] As a further improvement of the technical solution, the particle size of the special base material for protective slag is 0.05-0.2 mm.

[0019] Compared with the prior art, the present invention has the following beneficial effects: The special base material of the ultra-pure 409 series non-grinding protective slag uses synergistic lime. The higher reaction activity of active lime than calcium oxide is utilized. The reaction rate of active lime is controlled by compounding with praseodymium oxide. Triethanolamine phosphate is used to provide a protective layer to reduce the hygroscopicity of active lime and improve stability. Praseodymium oxide itself can improve the fluidity of the slag and absorb inclusions in the molten metal. Phosphorus-containing compounds can react with oxides and sulfides in the molten metal to adjust the viscosity of the slag, thereby effectively improving the surface quality of the ingot and achieving the effect of non-grinding. DETAILED DESCRIPTION

[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] The special base material of ultrapure 409 series non-grinding protective slag comprises the following components in parts by weight: 11-15 parts by weight of synergistic lime, 23-29 parts by weight of calcium oxide, 25-32 parts by weight of aluminum oxide, 12-16 parts by weight of silicon dioxide, 9-13 parts by weight of calcium fluoride, 6-8 parts by weight of magnesium oxide, 0.8-1.2 parts by weight of manganese carbonate, 2-5 parts by weight of zirconium oxide anti-corrosion agent, 1-3 parts by weight of boron trioxide viscosity regulator, 0.2-0.6 parts by weight of carbon powder reducing agent and 0.3-0.5 parts by weight of lithium oxide flux; wherein the synergistic lime is obtained by compounding active lime and praseodymium oxide in a mass ratio of 10:0.3-0.7 and bonding with triethanolamine phosphate.

[0022] Example 1: In this example, the specific preparation method of the special base material of the ultra-pure 409 series non-grinding protection slag is as follows: Prepare the following components: 13 parts by weight of enhanced lime, 29 parts by weight of calcium oxide, 32 parts by weight of aluminum oxide, 16 parts by weight of silicon dioxide, 13 parts by weight of calcium fluoride, 8 parts by weight of magnesium oxide, 1.2 parts by weight of manganese carbonate, 5 parts by weight of zirconium oxide anti-corrosion agent, 3 parts by weight of boron trioxide viscosity regulator, 0.6 parts by weight of carbon powder reducing agent and 0.5 parts by weight of lithium oxide flux; wherein the enhanced lime is obtained by compounding active lime and praseodymium oxide in a mass ratio of 10:0.3 and bonding with triethanolamine phosphate; the mass ratio of active lime to triethanolamine phosphate is 1:0.01; The praseodymium oxide and active lime powder are mixed in proportion, and the mixture is continuously stirred at 500 rpm / min by a stirrer to be fully mixed, and then placed in a muffle furnace for calcination at 400° C. for 4 hours. After the calcination is completed, the mixture is crushed into powder so that the particle size is less than 0.5 mm, and then added to a tetrahydrofuran solution containing triethanolamine phosphate with a mass fraction of 4%, and the mixture is continuously stirred for 30 minutes. After drying at 120° C. to constant weight, the mixture is ground and sieved to obtain synergistic lime; Add synergistic lime, calcium oxide, aluminum oxide, silicon dioxide, calcium fluoride, magnesium oxide, manganese carbonate, zirconium oxide anti-corrosion agent, boron trioxide viscosity regulator, carbon powder reducing agent and lithium oxide fluxing agent to the mixer, and mix all kinds of raw materials thoroughly. The filling amount of the mixer is 55% of the total capacity, the mixing speed is 50rpm / min, and the mixing time is 20min. Put the mixed raw materials into a high-temperature furnace and set the temperature curve for heating. The temperature curve includes 3 stages. The preheating stage is gradually heated from room temperature to 300℃, and the heating rate is 5℃ / min. The heating stage is heated from 300℃ to 1000℃, and the heating rate is 15℃ / min. The melting stage is heated from 1000℃ to the final melting temperature of 1500℃, and the heating rate is 5℃ / min. When the raw materials are completely melted, keep warm for 3h, use the rapid cooling method to make them quickly solidify, and then use a crusher to break them into small pieces, and the crushing speed is 500 rpm / min, crushing time 10min, the crushed small pieces are sieved through sieves of different apertures to obtain a special base material of ultra-pure 409 series non-grinding protective slag with a particle size of 0.1mm.

[0023] Example 2: In this example, the specific preparation method of the special base material of the ultra-pure 409 series non-grinding protection slag is as follows: Prepare the following components: 13 parts by weight of enhanced lime, 29 parts by weight of calcium oxide, 32 parts by weight of aluminum oxide, 16 parts by weight of silicon dioxide, 13 parts by weight of calcium fluoride, 8 parts by weight of magnesium oxide, 1.2 parts by weight of manganese carbonate, 5 parts by weight of zirconium oxide anti-corrosion agent, 3 parts by weight of boron trioxide viscosity regulator, 0.6 parts by weight of carbon powder reducing agent and 0.5 parts by weight of lithium oxide flux; wherein the enhanced lime is obtained by compounding active lime and praseodymium oxide in a mass ratio of 10:0.5 and bonding with triethanolamine phosphate; the mass ratio of active lime to triethanolamine phosphate is 1:0.03; The praseodymium oxide and active lime powder are mixed in proportion, and the mixture is continuously stirred at 500 rpm / min by a stirrer to be fully mixed, and then placed in a muffle furnace for calcination at 400° C. for 4 hours. After the calcination is completed, the mixture is crushed into powder so that the particle size is less than 0.5 mm, and then added to a tetrahydrofuran solution containing triethanolamine phosphate with a mass fraction of 5%, and stirred for 30 minutes. After drying at 120° C. to constant weight, the mixture is ground and sieved to obtain synergistic lime; Add synergistic lime, calcium oxide, aluminum oxide, silicon dioxide, calcium fluoride, magnesium oxide, manganese carbonate, zirconium oxide anti-corrosion agent, boron trioxide viscosity regulator, carbon powder reducing agent and lithium oxide fluxing agent to the mixer, and mix all kinds of raw materials thoroughly. The filling amount of the mixer is 55% of the total capacity, the mixing speed is 50rpm / min, and the mixing time is 20min. Put the mixed raw materials into a high-temperature furnace and set the temperature curve for heating. The temperature curve includes 3 stages. The preheating stage is gradually heated from room temperature to 300℃, and the heating rate is 5℃ / min. The heating stage is heated from 300℃ to 1000℃, and the heating rate is 15℃ / min. The melting stage is heated from 1000℃ to the final melting temperature of 1500℃, and the heating rate is 5℃ / min. When the raw materials are completely melted, keep warm for 3h, use the rapid cooling method to make them quickly solidify, and then use a crusher to break them into small pieces, and the crushing speed is 500 rpm / min, crushing time 10min, the crushed small pieces are sieved through sieves of different apertures to obtain a special base material of ultra-pure 409 series non-grinding protective slag with a particle size of 0.1mm.

[0024] Embodiment 3: In this embodiment, the specific preparation method of the special base material of the ultrapure 409 series non-grinding protection slag is as follows: Prepare the following components: 13 parts by weight of enhanced lime, 29 parts by weight of calcium oxide, 32 parts by weight of aluminum oxide, 16 parts by weight of silicon dioxide, 13 parts by weight of calcium fluoride, 8 parts by weight of magnesium oxide, 1.2 parts by weight of manganese carbonate, 5 parts by weight of zirconium oxide anti-corrosion agent, 3 parts by weight of boron trioxide viscosity regulator, 0.6 parts by weight of carbon powder reducing agent and 0.5 parts by weight of lithium oxide flux; wherein the enhanced lime is obtained by compounding active lime and praseodymium oxide in a mass ratio of 10:0.7 and bonding with triethanolamine phosphate; the mass ratio of active lime to triethanolamine phosphate is 1:0.05; The praseodymium oxide and active lime powder are mixed in proportion, and the mixture is continuously stirred at 500 rpm / min by a stirrer to be fully mixed, and then placed in a muffle furnace for calcination at 400° C. for 4 hours. After the calcination is completed, the mixture is crushed into powder so that the particle size is less than 0.5 mm, and then added to a tetrahydrofuran solution containing triethanolamine phosphate with a mass fraction of 6%, and stirred for 30 minutes. After drying at 120° C. to constant weight, the mixture is ground and sieved to obtain synergistic lime; Add synergistic lime, calcium oxide, aluminum oxide, silicon dioxide, calcium fluoride, magnesium oxide, manganese carbonate, zirconium oxide anti-corrosion agent, boron trioxide viscosity regulator, carbon powder reducing agent and lithium oxide fluxing agent to the mixer, and mix all kinds of raw materials thoroughly. The filling amount of the mixer is 55% of the total capacity, the mixing speed is 50rpm / min, and the mixing time is 20min. Put the mixed raw materials into a high-temperature furnace and set the temperature curve for heating. The temperature curve includes 3 stages. The preheating stage is gradually heated from room temperature to 300℃, and the heating rate is 5℃ / min. The heating stage is heated from 300℃ to 1000℃, and the heating rate is 15℃ / min. The melting stage is heated from 1000℃ to the final melting temperature of 1500℃, and the heating rate is 5℃ / min. When the raw materials are completely melted, keep warm for 3h, use the rapid cooling method to make them quickly solidify, and then use a crusher to break them into small pieces, and the crushing speed is 500 rpm / min, crushing time 10min, the crushed small pieces are sieved through sieves of different apertures to obtain a special base material of ultra-pure 409 series non-grinding protective slag with a particle size of 0.1mm.

[0025] Embodiment 4: In this embodiment, the specific preparation method of the special base material of the ultrapure 409 series non-grinding protection slag is as follows: Prepare the following components: 13 parts by weight of enhanced lime, 23 parts by weight of calcium oxide, 25 parts by weight of aluminum oxide, 12 parts by weight of silicon dioxide, 9 parts by weight of calcium fluoride, 6 parts by weight of magnesium oxide, 0.8 parts by weight of manganese carbonate, 2 parts by weight of zirconium oxide anti-corrosion agent, 1 part by weight of boron trioxide viscosity regulator, 0.2 parts by weight of carbon powder reducing agent and 0.3 parts by weight of lithium oxide flux; wherein the enhanced lime is obtained by compounding active lime and praseodymium oxide in a mass ratio of 10:0.5 and bonding with triethanolamine phosphate; the mass ratio of active lime to triethanolamine phosphate is 1:0.03; The praseodymium oxide and active lime powder are mixed in proportion, and the mixture is continuously stirred at 500 rpm / min by a stirrer to be fully mixed, and then placed in a muffle furnace for calcination at 400° C. for 4 hours. After the calcination is completed, the mixture is crushed into powder so that the particle size is less than 0.5 mm, and then added to a tetrahydrofuran solution containing triethanolamine phosphate with a mass fraction of 4%, and the mixture is continuously stirred for 30 minutes. After drying at 120° C. to constant weight, the mixture is ground and sieved to obtain synergistic lime; Add synergistic lime, calcium oxide, aluminum oxide, silicon dioxide, calcium fluoride, magnesium oxide, manganese carbonate, zirconium oxide anti-corrosion agent, boron trioxide viscosity regulator, carbon powder reducing agent and lithium oxide fluxing agent to the mixer, and mix all kinds of raw materials thoroughly. The filling amount of the mixer is 55% of the total capacity, the mixing speed is 50rpm / min, and the mixing time is 20min. Put the mixed raw materials into a high-temperature furnace and set the temperature curve for heating. The temperature curve includes 3 stages. The preheating stage is gradually heated from room temperature to 300℃, and the heating rate is 5℃ / min. The heating stage is heated from 300℃ to 1000℃, and the heating rate is 15℃ / min. The melting stage is heated from 1000℃ to the final melting temperature of 1500℃, and the heating rate is 5℃ / min. When the raw materials are completely melted, keep warm for 3h, use the rapid cooling method to make them quickly solidify, and then use a crusher to break them into small pieces, and the crushing speed is 500 rpm / min, crushing time 10min, the crushed small pieces are sieved through sieves of different apertures to obtain a special base material of ultra-pure 409 series non-grinding protective slag with a particle size of 0.2mm.

[0026] Embodiment 5: In this embodiment, the specific preparation method of the special base material of the ultrapure 409 series non-grinding protection slag is as follows: Prepare the following components: 11 parts by weight of enhanced lime, 29 parts by weight of calcium oxide, 32 parts by weight of aluminum oxide, 16 parts by weight of silicon dioxide, 13 parts by weight of calcium fluoride, 8 parts by weight of magnesium oxide, 1.2 parts by weight of manganese carbonate, 5 parts by weight of zirconium oxide anti-corrosion agent, 3 parts by weight of boron trioxide viscosity regulator, 0.6 parts by weight of carbon powder reducing agent and 0.5 parts by weight of lithium oxide flux; wherein the enhanced lime is obtained by compounding active lime and praseodymium oxide in a mass ratio of 10:0.5 and bonding with triethanolamine phosphate; the mass ratio of active lime to triethanolamine phosphate is 1:0.03; The praseodymium oxide and active lime powder are mixed in proportion, and the mixture is continuously stirred at 500 rpm / min by a stirrer to be fully mixed, and then placed in a muffle furnace for calcination at 400° C. for 4 hours. After the calcination is completed, the mixture is crushed into powder so that the particle size is less than 0.5 mm, and then added to a tetrahydrofuran solution containing triethanolamine phosphate with a mass fraction of 4%, and the mixture is continuously stirred for 30 minutes. After drying at 120° C. to constant weight, the mixture is ground and sieved to obtain synergistic lime; Add synergistic lime, calcium oxide, aluminum oxide, silicon dioxide, calcium fluoride, magnesium oxide, manganese carbonate, zirconium oxide anti-corrosion agent, boron trioxide viscosity regulator, carbon powder reducing agent and lithium oxide fluxing agent to the mixer, and mix all kinds of raw materials thoroughly. The filling amount of the mixer is 55% of the total capacity, the mixing speed is 50rpm / min, and the mixing time is 20min. Put the mixed raw materials into a high-temperature furnace and set the temperature curve for heating. The temperature curve includes 3 stages. The preheating stage is gradually heated from room temperature to 300℃, and the heating rate is 5℃ / min. The heating stage is heated from 300℃ to 1000℃, and the heating rate is 15℃ / min. The melting stage is heated from 1000℃ to the final melting temperature of 1500℃, and the heating rate is 5℃ / min. When the raw materials are completely melted, keep warm for 3h, use the rapid cooling method to make them quickly solidify, and then use a crusher to break them into small pieces, and the crushing speed is 500 rpm / min, crushing time 10min, the crushed small pieces are sieved through sieves of different apertures to obtain a special base material of ultra-pure 409 series non-grinding protective slag with a particle size of 0.1mm.

[0027] Embodiment 6: In this embodiment, the specific preparation method of the special base material of the ultra-pure 409 series non-grinding protection slag is as follows: Prepare the following components: 15 parts by weight of enhanced lime, 29 parts by weight of calcium oxide, 32 parts by weight of aluminum oxide, 16 parts by weight of silicon dioxide, 13 parts by weight of calcium fluoride, 8 parts by weight of magnesium oxide, 1.2 parts by weight of manganese carbonate, 5 parts by weight of zirconium oxide anti-corrosion agent, 3 parts by weight of boron trioxide viscosity regulator, 0.6 parts by weight of carbon powder reducing agent and 0.5 parts by weight of lithium oxide flux; wherein the enhanced lime is obtained by compounding active lime and praseodymium oxide in a mass ratio of 10:0.5 and bonding with triethanolamine phosphate; the mass ratio of active lime to triethanolamine phosphate is 1:0.03; The praseodymium oxide and active lime powder are mixed in proportion, and the mixture is continuously stirred at 500 rpm / min by a stirrer to be fully mixed, and then placed in a muffle furnace for calcination at 400° C. for 4 hours. After the calcination is completed, the mixture is crushed into powder so that the particle size is less than 0.5 mm, and then added to a tetrahydrofuran solution containing triethanolamine phosphate with a mass fraction of 4%, and the mixture is continuously stirred for 30 minutes. After drying at 120° C. to constant weight, the mixture is ground and sieved to obtain synergistic lime; Add synergistic lime, calcium oxide, aluminum oxide, silicon dioxide, calcium fluoride, magnesium oxide, manganese carbonate, zirconium oxide anti-corrosion agent, boron trioxide viscosity regulator, carbon powder reducing agent and lithium oxide fluxing agent to the mixer, and mix all kinds of raw materials thoroughly. The filling amount of the mixer is 55% of the total capacity, the mixing speed is 50rpm / min, and the mixing time is 20min. Put the mixed raw materials into a high-temperature furnace and set the temperature curve for heating. The temperature curve includes 3 stages. The preheating stage is gradually heated from room temperature to 300℃, and the heating rate is 5℃ / min. The heating stage is heated from 300℃ to 1000℃, and the heating rate is 15℃ / min. The melting stage is heated from 1000℃ to the final melting temperature of 1500℃, and the heating rate is 5℃ / min. When the raw materials are completely melted, keep warm for 3h, use the rapid cooling method to make them quickly solidify, and then use a crusher to break them into small pieces, and the crushing speed is 500 rpm / min, crushing time 10min, the crushed small pieces are sieved through sieves of different apertures to obtain a special base material of ultra-pure 409 series non-grinding protective slag with a particle size of 0.1mm.

[0028] Comparative Example 1: The method of Example 2 was adopted, but no synergistic lime was added to the special base material for protective slag.

[0029] Comparative Example 2: The method of Example 2 was adopted to prepare the enhanced lime without compounding with praseodymium oxide.

[0030] Comparative Example 3: The method of Example 2 was used to prepare the enhanced lime in which praseodymium oxide was compounded but not bonded with triethanolamine phosphate.

[0031] The present invention prepares a special base material of ultrapure 409 series non-grinding protective slag, and has a good effect of eliminating stainless steel surface defects in the application of protective slag preparation technology. The specific detection method is as follows: According to YB / T 185-2017 "Continuous Casting Mold Slag Viscosity Test Method", the viscosity of the mold slag is tested, and the viscosity is used to indirectly reflect the coverage effect of the mold slag. Too high or too low viscosity will affect its coverage effect, and then affect the surface quality of the stainless steel; prepare continuous casting billets of the same specifications as samples, ensure that the basic materials and continuous casting process parameters of all samples are the same, only change the type of mold slag used, keep the pulling speed, crystallizer vibration mode, cooling intensity of the secondary cooling zone and other variables consistent during the continuous casting process, and ensure that the only variable is the difference in the mold slag. After the continuous casting is completed, the surface of the billet is immediately subjected to magnetic particle inspection, the specimen is magnetized to generate a strong magnetic field, and magnetic powder is evenly applied to the surface of the specimen. The pattern formed by the magnetic powder on the surface of the specimen is observed, the location, size and distribution of the defects on the specimen are recorded, and the size of the defects is estimated. The formula: defect area percentage = (total defect area / total inspection area) × 100% is used to calculate the proportion of the defect area to the total inspection area.

[0032] The obtained data are shown in Table 1: Table 1 Performance data of Examples 1-6 and Comparative Examples 1-3

[0033] By comparing Examples 1-6 with Comparative Examples 1-3, it can be seen that in the special base material of the ultra-pure 409 series non-grinding protection slag, the synergistic lime has a significant impact on the non-grinding effect of stainless steel.

[0034] According to Examples 1-3, it can be seen that with the continuous change of the proportion of components in the enhanced lime, the effect of the stainless steel surface without grinding first increases and then decreases. This is because praseodymium oxide can improve the reaction rate of active lime, so that it can better protect the molten steel during the continuous casting process. Triethanolamine phosphate reduces the hygroscopicity of active lime through surface modification and improves its fluidity during the continuous casting process. At the same time, active lime, praseodymium oxide and triethanolamine phosphate can reduce non-metallic inclusions in the molten steel, thereby achieving the effect of reducing stainless steel surface defects. When the amount of praseodymium oxide added is too much, the reaction activity of active lime will be greatly reduced and the reaction rate will be too slow. When triethanolamine phosphoric acid is excessive, an excessively thick film layer will be formed on the surface of the active lime, affecting its contact and reaction with the molten steel, interfering with the function of the active lime, and then affecting the generation of stainless steel surface defects, and the effect of stainless steel surface without grinding cannot be achieved.

[0035] According to Example 2 and Example 4, it can be seen that with the continuous change of the content of other components in the special base material for protective slag, the effect of no grinding on the stainless steel surface does not change significantly. This is because the synergistic lime plays a leading role in the effect of no grinding on the stainless steel surface. Even if the content of other components in the special base material for protective slag changes, as long as the addition amount and proportion of the synergistic lime remain stable, its effect will not change significantly.

[0036] According to Example 2, Example 5 and Example 6, it can be seen that as the content of synergistic lime continues to change, the effect of no grinding on the stainless steel surface continues to change. This is because an appropriate amount of praseodymium oxide can effectively control the reaction rate of active lime while improving the fluidity of the special base material for protective slag, and an appropriate amount of triethanolamine phosphate can effectively protect the active lime while adsorbing non-metallic inclusions in the molten metal, thereby reducing the occurrence of surface defects of the stainless steel, thereby achieving the effect of no grinding. However, when praseodymium oxide and triethanolamine phosphate are excessive, they will become new inclusions, which is not conducive to the purity of the molten steel and the quality of the casting.

[0037] According to the above test experiments, Example 2 is used as the optimal example and compared with Comparative Examples 1-3 respectively.

[0038] By comparing Example 2 with Comparative Example 1, it can be seen that the special base material for protective slag without adding synergistic lime, the worse the effect of stainless steel surface without grinding. This is because active lime has higher reactivity than ordinary calcium oxide and can react with impurities in molten steel. Praseodymium oxide can be compounded with active lime to control its reaction rate. Triethanolamine phosphate can reduce the hygroscopicity of active lime and improve the uniformity and stability of slag. The special base material for protective slag without adding synergistic lime cannot provide the beneficial effects of high reactivity, improved fluidity and reduced inclusions due to the lack of synergistic lime that can more effectively absorb inclusions in molten steel, resulting in defects on the stainless steel surface, which in turn makes the effect of stainless steel surface without grinding worse.

[0039] By comparing Example 2 with Comparative Example 2, it can be seen that the more praseodymium oxide is not compounded in the preparation of the enhanced lime, the worse the effect of the stainless steel surface without grinding. This is because the presence of praseodymium oxide can control the reaction rate of the active lime to prevent it from being consumed too quickly or reacting too violently. At the same time, praseodymium oxide can improve the fluidity of the special base material for protective slag, making it easier to cover the surface of the molten steel and prevent the secondary oxidation of the molten steel. Without the control of the composite layer of praseodymium oxide, the active lime reacts violently at high temperature, which is not conducive to the stability of the components of the special base material for protective slag, and thus the effect of the stainless steel surface without grinding becomes worse.

[0040] By comparing Example 2 and Comparative Example 3, it can be seen that the more praseodymium oxide is compounded with the enhanced lime but not bonded with triethanolamine phosphate, the worse the effect of no grinding on the stainless steel surface. This is because triethanolamine phosphate can form a hydrophobic film on the surface of the active lime, reduce the hygroscopicity of the active lime, and prevent it from absorbing moisture during storage and transportation, thereby avoiding agglomeration. At the same time, triethanolamine phosphate can improve the lubricity of the special base material for protective slag, making it easier to flow and evenly cover the surface of the molten steel during the continuous casting process to prevent oxidation. In addition, it can form phosphorus-containing compounds with rare earth elements, which is helpful to remove inclusions in the molten steel. Without triethanolamine phosphate, the active lime has strong hygroscopicity, poor fluidity, insufficient lubricity, and its ability to absorb inclusions deteriorates, so the effect of no grinding on the stainless steel surface is worse.

[0041] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments, and the above embodiments and descriptions are only preferred examples of the present invention, and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. Special base material for ultra-pure 409 series non-grinding protective slag, characterized by: The invention comprises the following components in parts by weight: 11-15 parts by weight of synergistic lime, 23-29 parts by weight of calcium oxide, 25-32 parts by weight of aluminum oxide, 12-16 parts by weight of silicon dioxide, 9-13 parts by weight of calcium fluoride, 6-8 parts by weight of magnesium oxide, 0.8-1.2 parts by weight of manganese carbonate, 2-5 parts by weight of zirconium oxide anti-corrosion agent, 1-3 parts by weight of boron trioxide viscosity regulator, 0.2-0.6 parts by weight of carbon powder reducing agent and 0.3-0.5 parts by weight of lithium oxide flux; Among them, the enhanced lime is obtained by compounding active lime and praseodymium oxide in a mass ratio of 10:0.3-0.7 and bonding with triethanolamine phosphate.

2. The special base material of ultrapure 409 series non-grinding protection slag according to claim 1 is characterized in that: The specific preparation method of the enhanced lime is as follows: Praseodymium oxide and active lime powder are mixed in proportion, stirred continuously at 300-500 rpm / min with a stirrer to make them fully mixed, and then placed in a muffle furnace for calcination. After calcination, the mixture is crushed into powder with a particle size of less than 0.5 mm, and then added to a tetrahydrofuran solution containing triethanolamine phosphate, and stirred for 20-30 minutes. Dry at 100-120°C to constant weight. After drying, the mixture is ground and sieved to obtain enhanced lime.

3. The special base material of ultrapure 409 series non-grinding protection slag according to claim 2 is characterized in that: The calcination temperature of the muffle furnace is 400-600° C., and the calcination time is 2-4 hours.

4. The special base material of ultrapure 409 series non-grinding protection slag according to claim 2 is characterized in that: The mass fraction of the tetrahydrofuran solution containing triethanolamine phosphate is 4-6%.

5. The special base material of ultrapure 409 series non-grinding protection slag according to claim 1 is characterized in that: The mass ratio of the active lime to triethanolamine phosphate is 1:0.01-0.

05.

6. The special base material of ultrapure 409 series non-grinding protection slag according to claim 1 is characterized in that: The specific preparation method of the special base material for protective slag is as follows: Add synergistic lime, calcium oxide, aluminum oxide, silicon dioxide, calcium fluoride, magnesium oxide, manganese carbonate, zirconium oxide anti-corrosion agent, boron trioxide viscosity regulator, carbon powder reducing agent and lithium oxide flux into the mixer, mix all the raw materials thoroughly, put the mixed raw materials into a high-temperature furnace, set the temperature curve for heating, keep the heat for 1-3 hours after the raw materials are completely melted, use the rapid cooling method to quickly solidify them, then use a crusher to break them into small pieces, and sieve the broken small pieces through sieves of different apertures to obtain the special base material of ultra-pure 409 series non-grinding protective slag.

7. The special base material of ultrapure 409 series non-grinding protection slag according to claim 6 is characterized in that: The filling amount of the mixer is 45-55% of the total capacity, the mixing speed is 30-50 rpm / min, and the mixing time is 20-30 min.

8. The special base material of ultrapure 409 series non-grinding protection slag according to claim 6, characterized in that: The temperature curve includes three stages: the preheating stage is gradually heated from room temperature to 200-300°C, with a heating rate of 5-10°C / min; the heating stage is heated from 300°C to 800-1000°C, with a heating rate of 10-15°C / min; the melting stage is heated from 1000°C to the final melting temperature of 1400-1500°C, with a heating rate of 1-5°C / min.

9. The special base material of ultrapure 409 series non-grinding protection slag according to claim 6, characterized in that: The crushing speed of the crusher is 500-1000rpm / min, and the crushing time is 5-10min.

10. The special base material of ultrapure 409 series non-grinding protection slag according to claim 6, characterized in that: The particle size of the special base material for protective slag is 0.05-0.2mm.